2016
DOI: 10.1002/er.3586
|View full text |Cite
|
Sign up to set email alerts
|

Comparative life cycle assessment of hydrogen pathways from fossil sources in China

Abstract: Summary Emissions of multiple hydrogen production pathways from fossil sources were evaluated and compared with that of fossil fuel production pathways in China by using the life cycle assessment method. The considered hydrogen pathways are gasoline reforming, diesel reforming, natural gas reforming, soybean‐derived biodiesel (s‐biodiesel) reforming, and waste cooking oil‐derived biodiesel reforming. Moreover, emissions and energy consumption of fuel cell vehicles utilizing hydrogen from different fossil sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Additionally, 27% of the case studies accounted for on-site hydrogen production processes (97/355), including on-site thermochemical processes (41/97) and on-site electrochemical processes (56/97). However, only five case studies addressed on-board auto thermal reforming [65]. Moreover, only 9% of the total centralized thermochemical case studies (13/140) involved carbon capture and sequestration (CCS), and considered SR and gasification [35,36,46,56,62,67,71,84].…”
Section: System Boundarymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, 27% of the case studies accounted for on-site hydrogen production processes (97/355), including on-site thermochemical processes (41/97) and on-site electrochemical processes (56/97). However, only five case studies addressed on-board auto thermal reforming [65]. Moreover, only 9% of the total centralized thermochemical case studies (13/140) involved carbon capture and sequestration (CCS), and considered SR and gasification [35,36,46,56,62,67,71,84].…”
Section: System Boundarymentioning
confidence: 99%
“…Most studies (252) used in this review did not specify the fuel cell type. PEMFC technology was explicitly mentioned for hydrogen use in 36 case studies [21-23, 27, 29, 38, 44, 56, 61, 70], and only five case studies considered SOFCs [65]. As shown in the 'hydrogen use for road transport' stage in figure 5, four types of powertrains were considered for cars: FCV (175/230), FCHEV (9/230), ICEV (34/230), and HICEV (7/230).…”
Section: System Boundarymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature, different sources of hydrogen production such as electrolysis, biomass gasification, steam methane reforming, and coal gasification are studied here [49]. GHG emission factors for hydrogen production from various methods are given in Table 5 [50]. The impact of these sources on the overall life cycle GHG emissions is shown in Figure 4.…”
Section: Changing Enzyme Configurationmentioning
confidence: 99%
“…Daniele et al [7] evaluated the life-cycle performance of three different types of vehicles based on wind power electrolysis of water for hydrogen production and the results showed that hydrogen fuel is an excellent decarbonization solution. Both Dong et al [8] and Huang et al [9] performed life cycle analysis of the environmental impact of fuel cell vehicle energy under different fossil fuel-based hydrogen fuel paths. The results showed that supplying fuel cell vehicles with hydrogen from natural gas reforming is the most advantageous in terms of energy saving and emission reduction.…”
Section: Introductionmentioning
confidence: 99%